Ethnoknowledge associated with the use of latex from janaúba (Himatanthus Drasticus (Mart.) Plumel) and its reflections on the marketing of its pharmacological formulations (Research, Society and Development, 2022)
This research brings a bibliographic survey on the ethnoknowledge of medicinal plants and, in particular, on the latex of the species Himatanthus Drasticus (Mart.) Plumel, popularly known as Janaúba. Some articles and electronic documents available in a scientific database in the last 10 years were analyzed. Therefore, it was noted that it is noticeable that janaúba is a medicinal plant with great benefits for humans, but when it comes to the commercialization of pharmacological formulations, it is still little investigated. Therefore, this medicinal plant needs further studies on the phytochemical test and the elucidation of the therapeutic potential of Janaúba latex.